Menguji Konstitusionalitas Peraturan Pemerintah Pengganti Undang-Undang (Lex Jurnalica, 2014)
AbstractThe existence of a government regulation a substitute for laws (Perpu) in the system of the legislation is poured in The Constitution of The Republic of Indonesia 1945. Perpu be made by the President in a state of precarious and force. Perpu gave birth to the legal norms and as a new legal norms may pose new legal status, a new legal relationship, and as a result of the new law. Legal norms were born since the Perpu passed and fate of these legal norms are subject to the approval of the House of Representatives (DPR) to accept or reject the Perpu legal norms, however prior to the opinion of the House of Representatives to reject or approve the Perpu, these legal norms are legitimate and valid as legislation. Because inflicts legal norms concerning force equal to the norms and laws against Perpu contained in The Constitutional Court can test whether perpu opposed to materially with the 1945 Constitution. As the guardian of constitution and interpreter of the 1945 Constitution, The Constitutional Court has the authority to test perpu against the 1945 Constitution before the presence of denial or approval by the House of Representatives, and after the approval of the house of representatives for perpu has been into law.Keywords: government regulation substitute for laws, the constitution court, constitutional reviewÂ Â AbstrakKeberadaan Peraturan Pemerintah Pengganti Undang-Undang (Perpu) dalam sistem peraturan perundang-undangan dituangkan dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 (UUD 1945). Perpu tersebut dibuat oleh Presiden dalam keadaan â€œkegentingan yang memaksaâ€. Perpu melahirkan norma hukum dan sebagai norma hukum baru akan dapat menimbulkan status hukum baru, hubungan hukum baru, dan akibat hukum baru. Norma hukum tersebut lahir sejak Perpu disahkan dan nasib dari norma hukum tersebut tergantung kepada persetujuan Dewan Perwakilan Rakyat (DPR) untuk menerima atau menolak norma hukum Perpu, namun demikian sebelum adanya pendapat DPR untuk menolak atau menyetujui Perpu, norma hukum tersebut adalah sah dan berlaku seperti Undang-Undang. Oleh karena lahirnya Perpu dapat menimbulkan norma hukum yang kekuatan mengikatnya sama dengan Undang-Undang maka terhadap norma yang terdapat dalam Perpu tersebut, Mahkamah Konstitusi dapat menguji apakah Perpu bertentangan secara materiil dengan UUD 1945. Sebagai pengawal dan penafsir UUD 1945, Mahkamah Konstitusi berwenang untuk menguji Perpu terhadap UUD 1945 sebelum adanya penolakan atau persetujuan oleh DPR, dan setelah adanya persetujuan DPR karena Perpu tersebut telah menjadi Undang-Undang.Kata kunci:Â Â Â Â Â Â Â Â  peraturan pemerintah pengganti Undang-Undang, mahkamah konstitusi, pengujian konstitusional